Comparative analysis of four types of mesoscale eddies in the North Pacific Subtropical Countercurrent region - part II seasonal variation - Sun, Wenjin; An, Mengxuan; Liu, Jishan; Liu, Jie; Yang, Jingsong; Tan, Wei; Sian, Kenny T. C. Lim Kam; Ji, Jinlin; Liu, Yu; Dong, Changming (Frontiers in Marine Science, 2023)
The North Pacific Subtropical Countercurrent area (STCC) is high in mesoscale eddy activities. According to the rotation direction of the eddy flow field and the sign of temperature anomaly within the eddy, they can be divided into four categories: cyclonic cold-core eddy (CCE), anticyclonic warm-core eddy (AWE), cyclonic warm-core eddy (CWE) and anticyclonic cold-core eddy (ACE). CCE and AWE are called normal eddies, and CWE and ACE are named abnormal eddies. Based on the OFES data and vector geometry automatic detection method, we find that at the sea surface, the maximum monthly number of the CCE, AWE, CWE, and ACE occurs in December (765.70 ± 52.05), January (688.20 ± 82.53), August (373.40 ± 43.09) and August (533.00 ± 56.92), respectively. The number of normal eddies is more in winter and spring, and less in summer and autumn, while abnormal eddies have the opposite distribution. The maximum rotation velocity of the four types of eddies appears in June (11.71 ± 0.75 cm/s), June (12.24 ± 0.86 cm/s), May (10.63 ± 0.99 cm/s) and June (9.97 ± 0.91 cm/s), which is fast in winter and spring. The moving speed of the four types of eddies is almost similar (about 10 11 cm/s). The amplitude of normal and abnormal eddies is both high in summer and autumn, and low in winter and spring, with larger amplitudes in normal than abnormal eddies. The eccentricity (defined as the eccentricity of the ellipse obtained by fitting the eddy boundary) of the four types of eddies is also close to each other, and their variation ranges from 0.7 to 0.8, with no apparent seasonal variation. The vertical penetration depth, which has no significant seasonal difference, is 675.13 ± 67.50 m in cyclonic eddies (CCE and CWE), which is deeper than that 622.32 ± 81.85 m in anticyclonic eddies (ACE and AWE). In addition, increasing the defined temperature threshold for abnormal eddies can significantly reduce their numbers but does not change their seasonal variation trend.